Equine Herpesvirus-1 Induced Respiratory Disease in Dezhou Donkey Foals: Case Study from China, 2024 - Lian Ruan; Liangliang Li; Rongze Yang; Anrong You; Muhammad Zahoor Khan; Yue Yu; Li Chen; Yubao Li; Guiqin Liu; Changfa Wang; Tongtong Wang (Veterinary Sciences)
Equine herpesvirus-1 (EHV-1) is a significant pathogen that causes substantial economic losses in the equine industry worldwide, which leads to severe respiratory diseases and abortions in horses. However, reports of EHV-1 infection in donkeys are limited, particularly in China. This case study reported an EHV-1-induced respiratory disease in Dezhou donkey foals in Shandong Province, China, in July 2024. Three one-month-old foals exhibited high fever, nasal discharge, and respiratory distress, with a 100% mortality rate. The causative agent, strain LC126, was isolated from a one-month-old donkey foal exhibiting severe respiratory disease. Phylogenetic analysis of the EHV-1 isolate LC126 showed close similarity to EHV-1. Overall, our study revealed that EHV-1 can cause respiratory distress as well as death in donkeys. The study underscores the emerging threat of EHV-1 in donkeys and highlights the need for veterinarians and breeders to give proper attention to the potential threat of EHV-1 outbreaks.